2015
DOI: 10.1116/1.4921278
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cell membrane permeability using a cell-solution electrode for generating atmospheric-pressure plasma

Abstract: The cell membrane permeability, which is strongly related to gene transfection, is improved using a cell-solution electrode for generating atmospheric-pressure plasma (APP) just above the solution. In the case of the floating cells, the cell membrane permeability is significantly improved by the cell-solution electrode APP compared with the conventional diffusion type APP, because the distance between the plasma generation area and the cell solution surface becomes short, which could reduce the radial diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…These scavengers were purchased from Sigma-Aldrich (St. Louis, MO, USA), including sodium pyruvate for H 2 O 2 50; mannitol for OH50; tiron for O23456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051; and N-acetyl cysteine (NAC) as a general ROS scavenger5253. These scavengers are specific with little cross-reactivity to other ROS, so they are used in many protocols for investigating particular ROS functions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scavengers were purchased from Sigma-Aldrich (St. Louis, MO, USA), including sodium pyruvate for H 2 O 2 50; mannitol for OH50; tiron for O23456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051; and N-acetyl cysteine (NAC) as a general ROS scavenger5253. These scavengers are specific with little cross-reactivity to other ROS, so they are used in many protocols for investigating particular ROS functions.…”
Section: Methodsmentioning
confidence: 99%
“…However, Sakai reported that the plasma could induce DNA strand breaks in a PBS solution27. A recent study showed that by using the cell-solution electrode, plasma jet could improve cell permeability compared with the conventional diffusion type plasma31. Some publications have discussed transdermal drug delivery by cold atmosphere plasma323334.…”
mentioning
confidence: 99%
“…observed the improvement of the cell membrane permeability using a cell-solution electrode CAP and they attributed this to the increase of the electric field and the density of the short-lived ROS reaching the cells in the solution 11 . Moreover, Hong et al .…”
Section: Introductionmentioning
confidence: 99%
“…Plasma medicine is a rapidly emerging field, and a number of researchers have reported innovative applications of non-equilibrium atmospheric-pressure plasma (APP) 1 2 3 4 , including its use in the selective killing of cancer cells 5 , in blood coagulation for minimally invasive surgery, in assisting wound healing and tissue regeneration 6 , and as a gene transfer tool 7 8 9 . Non-equilibrium APP has a higher electron temperature (~several eV) than gas (ion) temperature 10 .…”
mentioning
confidence: 99%